Inovasi Pembelajaran Tahfiz Alquran Dengan Metode Menjaga, Mengulang, Menghafal (M3) Di Pondok Pesantren - Rusadi, Bobi Erno; Rahmawati, Tia (Yayasan Rahmat Islamiyah, 2023)
This study aims to describe the innovation of learning tahfiz M3 method (Keeping Repeating Memorization) at Pondok Pesantren Modern Al- Ghozali Bogor. The research method used is qualitative method. Data collection techniques were conducted through interviews, non-participatory observation, and documentation. The findings of this study indicate that tahfiz learning with the M3 method is carried out starting from the planning, implementation and evaluation processes. In planning, teachers prepare all learning resources and learning media used. At the implementation stage, the teacher begins by reading al-ma'tsurat, then invites students to murajaah and add (ziyadah) memorization. Furthermore, the evaluation of Quranic memorization learning is carried out by holding monthly meetings with all Quranic memorization teachers where this meeting will discuss developments, problems faced, solutions, Quranic memorization learning activities, and others related to Quranic memorization. Then, weekly evaluations are held with all students to evaluate mutabaah book reports in one week. The Tahfiz report card is distributed at the end of each semester as an evaluation material for students or parents in the process of learning Tahfiz Alquran during one semester.